2020
DOI: 10.1111/srt.12951
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the skin parameters of Caucasian women from Central Europe

Abstract: Background The human skin is greatly affected by external factors such as UV radiation (UVR), ambient temperature (T), and air humidity. These factors oscillate during the year giving rise to the seasonal variations in the skin properties. The aim of this study was to evaluate the effect of seasons, environmental T, relative and absolute humidity on the skin parameters of Caucasian women, perform a literature review and discuss the possible factors lying behind the found changes. Materials and Methods We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 105 publications
3
10
0
Order By: Relevance
“… 18 , 19 Finally, one study found TEWL of the forehead was significantly lower during spring months. 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 18 , 19 Finally, one study found TEWL of the forehead was significantly lower during spring months. 20 …”
Section: Resultsmentioning
confidence: 99%
“…18,19 Finally, one study found TEWL of the forehead was significantly lower during spring months. 20 First, Song et al 16 examined how skin integrity differed between summer and winter in healthy Korean males. All 100 subjects rested in a room 20-24°C with humidity from 40% to 60% for 30 min.…”
Section: Seasonal Variation In Tewlmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted on adults, the SCH and TEWL were best during spring, and sebum secretion was the highest during summer and decreased during autumn and winter (Dolečková et al, 2021). Another study conducted in Japan reported that sebum secretion increased in adults during spring and winter (Kenjo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%